A Descriptive Study to Assess the Stress and Coping Mechanism Due to Lockdown among School Going Children - Dipali Dumbre1 , Sharadha Ramesh1 , Ranjana Chavan1 , Mangesh Jabade1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Corona virus is an infectious disease came in December 2019 in China. People with infectionget the respiratory problem but doesn’t show any symptoms and not required any treatment. But those arehaving underlying problems like diabetes mellitus, pregnant women and children are having risk of gettingcomplication with corona virus infection. The government announced immediate lockdown in country forthe prevention of spread of infection and has change life of million children into complete confusion. Manyare starving for the foods and calling for the help as the country shuts down to battle the pandemic. Thelargest child population is in India with 472 million, and Promoters say due to this immediate lockdownmany children has disturbed. A assessment survey was done among parents has shown that children’s arehaving more anxiety, increased use of TV and Social media and changed eating pattern. Another studyshows that 37% of the children are psychological disturb and 88% spent most of the time on using socialnetworking sitesObjective: To assess stress and coping mechanism due to lockdown among school going children.Methodology: A Descriptive Research Approach is used. 60 samples were selected by using Non ProbabilityPurposive Sampling Technique. Data was taken using Stress and coping mechanism questinnarrie throughonline Google form. Result: The study findings show that majority (41%) of the children answered werefrom 10th standard ,30% from 9th standard ,17% from 8th standard and 12% from 7th standard. It also showsthat 58% were male and 42% were girl children. The assessment of stress is done by using the questionnairebased on the stress parameter like physical, psychological, family, financial burden, academics, quarrel withsiblings, food .The rating were selected through 5 point likert scale from strongly disagree to Strongly agree.The result of stress due to lockdown findings shows that in majority of the children are strongly agree andagree with the physical stress, psychological stress ,family stress, stress due to financial burden, Academicsstress, quareel with sibling and food due to lockdown. The children were using the many coping mechanismto relive this stress and majority of the children were using the coping mechanisms like using social media,exercise, doing study, doing household work, entertainment.Conclusion: The findings indicate that the questionnaire was effective in assessing the stress and copingmechanism among school going children. The study also concluded that majority of the children are havingthe stress due to lockdown but they are also using the coping mechanism to reduce this stress